Using systemic structural activity approach in identifying strategies enhancing human performance in mining production drilling activity. - Sanda, M. A.; Johansson, J.; Johansson, B.; Abrahamsson, L. (My University, 2014)
This article seeks to identify performance-enhancing strategies that could be used to improve and optimise human–technology collaboration in rock drilling ‘activity’ in deep mines. Results from the analysis of miners’ motor actions during rock drilling activity showed that by using procedurally driven strategies, they were able to perform simultaneously two specific tasks that required high levels of concentration and visual control in the normal visual field available to them from inside the protective cabin of the high-technology equipment they were using. The miners simultaneously combine their mental actions and motor actions in recognising and remedying the constraining effects of unfamiliar stimuli during the rock drilling task. It is concluded that the functional efficiency and effectiveness of rock drilling as well as the miner’s productive performance in future automated and digitised deep mines could be enhanced by identifying the procedural characteristics of their performance-enhancing actions and operational strategies.
Keywords: systemic structural analysis; procedural and declarative knowledge; digitised deep mine; performance- enhancing strategy